Structures controlling volcanic activity within Masaya caldera, Nicaragua - Guillermo Caravantes González; Hazel Rymer; Jeffrey Zurek; Susanna Ebmeier; Stephen Blake; Glyn Williams-Jones (Volcanica, 2019)
Geophysical and geological observations collected in 2007-2012 shed light on the mechanisms controlling the style and location of eruptions within the Las Sierras-Masaya Caldera complex, Nicaragua. These results confirm a hypothesised ~3.5 km diameter structure with features compatible with the presence of a ring fracture (50-65°, with inward-dipping bounding walls). A central block is bound by this fracture and defines an incipient nested caldera related to the emptying of the magma chamber following the last Plinian eruption (1.8 ka). The prolongation of the Cofradías fault from the Managua graben represents the most significant structure on the floor of Masaya caldera. Current activity, including a convecting lava lake, largely depends on the interplay between the extensional stress regime associated with the Managua graben and deformation along the inner caldera bounding fault. This high spatial resolution survey uses a novel combination of geophysical methodologies to identify previously overlooked foci for future volcanic activity at Masaya.